Comparison of fine needle aspiration cytology and histopathology in neck mass diagnosis - Meher Ullah, M.; Ahmed, Jalal; Mondal, Satya Ranjan; Aman, Asif; Qurashi, Sabrina Akhter; Alam, A. B. M. Khurhid (International Surgery Journal, 2025)
Background: Neck masses are common clinical presentations with a wide range of etiologies, including benign, inflammatory and malignant conditions. Fine needle aspiration cytology (FNAC) is widely used as a first-line diagnostic tool, but histopathology remains the gold standard. This study aimed to evaluate the diagnostic performance of FNAC by comparing it with histopathological findings in patients with neck masses. Methods: This descriptive study was conducted at Dhaka Medical College Hospital from July 2019 to June 2020. A total of 100 patients with clinically significant neck masses were enrolled through purposive sampling. FNAC was performed on all participants, followed by surgical excision and histopathological examination. Diagnostic metrics, including sensitivity, specificity, predictive values and accuracy, were calculated. Results: Thyroid lesions were the most frequent diagnosis by FNAC (42%), followed by lymphadenopathy (35%) and salivary gland lesions (13%). FNAC identified 68% of cases as benign/inflammatory and 32% as malignant, while histopathology confirmed 73% as benign and 27% as malignant. The overall diagnostic accuracy of FNAC was 87.00%, with sensitivity of 94.12%, specificity of 71.88%, PPV of 87.67% and NPV of 85.19%. The correlation between FNAC and histopathology was statistically significant (p=0.001). Conclusions: FNAC is a reliable, accessible and accurate screening tool for neck mass evaluation. However, histopathological confirmation remains essential, especially for definitive diagnosis and treatment planning.